Peran Broadband Learning Center dalam community development - Putu Aditya Ferdian Ariawantara (Masyarakat, Kebudayaan dan Politik, 2017)
Answering the need of non-formal education or courses that reach all levels of society in the field of information and communication technology (ICT), the Government of Surabaya through the Department of Communications and Information Technology has developed Broadband Learning Center (BLC). BLC plays significant role in community development Surabaya since they provide media for public to choose training program which they can register independently or in groups training for free. This study aims to describe the framework in BLC as the implementation of e-governance performed by Government of Surabaya and to explore the role of BLC in community development process in achieving e-governance. The method used by researcher is qualitative approach with descriptive research type, focusing on Department of Communications and Information Technology, BLC Rumah Bahasa, BLC Taman Prestasi and BLC Taman Flora. This research reveals that BLC is facilitated with openness service to IT and various courses to enhance capacity and capability to utilize computer, and to increase public participation in using IT based program.